Grimontia sedimenti sp. nov., isolated from benthic sediments near coral reefs south of Kuwait. Issue 3 (25th March 2021) - Mahmoud, Huda; Jose, Liny; Eapen, Susan
Abstract : A Gram-stain-negative, rod and rod-curved shaped motile bacterium designated strain S25 T was obtained from benthic sediment collected near the Kubbar Island coral reefs south of Kuwait. Phenotypic analysis revealed that strain S25 T was slightly halophilic, mesophilic and facultative anaerobic, fermenting d -glucose, d -ribose, d -mannose, d -mannitol, maltose, fructose, gentiobiose, cellobiose, melibiose, trehalose and sucrose. It was positive for oxidase and indole production and negative for arginine dihydrolase and lysine and ornithine decarboxylases. It contained C16 : 1  ω 7 c /C16 : 1  ω 6 c (summed feature 3), C18 : 1  ω7 c (summed feature 8) and C16 : 0 as the major fatty acids. Strain S25 T grew optimally at 30 °C and pH 8 in the presence of 3 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA sequences revealed that strain S25 T is related to species of the genus Grimontia, having 99.15 % similarity to ' Grimontia indica ' AK16 T, 99.08 % to Grimontia celer 96-237 T and 98.66 % to Grimontia marina IMCC 5001 T . The DNA G+C content was 48.8 mol% and the full genome analysis for the strain S25 T showed that the bacterium has a genome size of 5 158 621 bp and contains 4730 predicted protein-encoding genes. The average nucleotide identity values between the S25 T genome and the genomes of its nearest matches ranged between 81.39 and 94.16 %. The strain was distinguishable from the phylogenetically related genera through differences in several phenotypic properties. On the basis of the phenotypic, phylogenetic and genetic data, strain S25 T represents a novel species in the genus Grimontia, for which the name Grimontia sedimenti sp. nov. is proposed. The type strain of Grimontia sedimenti is S25 T (=DSM 28878 T =LMG 28315 T ).